(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
This paper analyses unemployment rate among the youth in Volyn region. Factors affecting competitiveness of graduates on the local job market are investigated. Taking into account the standarts that are required on the local job market, it is proved that marketing conception of educational institutions needs further review. In this paper marketing efforts for improving competitiveness of graduates are suggested. Marketing of the university should investigate the situation on the job market, promote the graduates on the labour market and implement set of measures for providing graduates with job positions in enterprises (institutions and establishments). Special consideration is given to preparing the graduates for self-employment the latter being regarded as one of the ways of reducing unemployment rate in the region.